Activation of Carbon Using Microwave-Assisted Hydrochloric Acid for Urea Adsorbtion - Regawa Bayu Pamungkas; Kiswatul Kharimah; Endar Puspawiningtiyas (Research in Chemical Engineering, 2022)
The activation of activated carbon using microwave-assisted hydrochloric acid (HCl) has been carried out. This objective of this study was to investigate the effects of the concentration of HCl (1M to 6 M) and time of microwave irradiation (5 to 25 mins) on the iodine number and urea adsorption. The results showed that the concentration of HCl had a significant effect on the quality of the activated carbon. Activation of carbon using 6 mol/L of HCl resulted the iodine adsorption capacity of 1002 mg/g and urea adsorption of 99 mg/g. Microwave irradition time also has a significant effect on the quality of activated carbon. The best microwave irradiation time showed at 25 minutes that resulted in iodine adsorption capacity of 1112 mg/g and urea adsorption capacity of 97 mg/g.